The Application of multiple Intelligences Approach in an EFL Classroom - Gusti Nur Hafifah (Didaktis: Jurnal Pendidikan dan Ilmu Pengetahuan, 2015)
Multiple Intelligences Approach is one of the teaching Methods that was adapted from the psychological theory by Howard Gardner, who found and developed MI as the new Paradigm in Intelligence. Multiple Intelligences Strategy giveteachers the chance to discover, value and enhance the talents of all learners through eight different intelligences that they have. This study attempts to observe the Multiple Intelligences teaching Strategy being used by an English Teacher in an EFL Classroom. To what extent the Teacher applied the eight Multiple Intelligences Teaching Strategies in the English Teaching Learning Process. The MI Teaching Strategies are;Linguistic Strategy, Logical/ Mathematical Strategy, Visual/Spatial Strategy, Bodily/Kinesthetic Strategy, Musical Strategy, Interpersonal Strategy, Intra-personal Strategy, and Naturalist Strategy.Since this study was descriptive qualitative study, the researcher described and evaluated the existing phenomena during the observation and also the result of the interview. In this case, the subject of the study wasthe English Teacher in SMP Muhamadiyah 9, which published its school as a Multiple Intelligences Based School. The observation was done in nine meetings of English Subject, involving 2 different classes. Furthermore, the instrument used was the researcher herself as the observer of the study and interviewer.The result showed that the MI Teaching Strategy was not applied optimally in the classroom. Teacher applied some seven from the Eight Intelligences Strategies being observed, such as Linguistic Strategy, Logical/ Mathematical Strategy, Visual/Spatial Strategy, Bodily/Kinesthetic Strategy, Interpersonal Strategy, Intrapersonal Strategy, and Naturalist Strategy. The Musical Intelligence Strategy was not found on the observation since teacher’s voice was the only source of music and there wasn’t any use of sounds music or rhythm during the teaching. And the Linguistic Intelligence Strategy was the most dominated strategy as language was the main subject of the lesson. It can be concluded that MI Strategies depend very much on the teacher ability in creating creative and innovative ideas in developing teaching techniques that suitable to the variety of intelligence that the students have. Key Words: Multiple Intelligences; Linguistic, Linguistic, Logical/ Mathematical, Visual/Spatial, Bodily/Kinesthetic, Musical, Interpersonal, Intrapersonal, and Naturalist Intelligences, Teaching Strategies.